The Post-thrombotic Syndrome-Prevention and Treatment: VAS-European Independent Foundation in Angiology/Vascular Medicine Position Paper - Cosmi, Benilde; Stanek, Agata; Kozak, Matja; Wennberg, Paul W.; Kolluri, Raghu; Righini, Marc; Poredos, Pavel; Lichtenberg, Michael; Catalano, Mariella; De Marchi, Sergio; Farkas, Katalin; Gresele, Paolo; et al. (Frontiers in Cardiovascular Medicine, 2022)
Abstract Importance: The post-thrombotic syndrome (PTS) is the most common long-term complication of deep vein thrombosis (DVT), occurring in up to 40-50% of cases.There are limited evidence-based approaches for PTS clinical management Objective: To provide an expert consensus for PTS diagnosis, prevention, and treatment. Evidence-review: MEDLINE, Cochrane Database review, and GOOGLE SCHOLAR were searched with the terms “post-thrombotic syndrome” and “post-phlebitic syndrome” used in titles and abstracts up to September 2020. Filters were: English, Controlled Clinical Trial / Systematic Review / Meta-Analysis / Guideline. The relevant literature regarding PTS diagnosis, prevention and treatment was reviewed and summarized by the evidence synthesis team. On the basis of this review, a panel of 15 practicing angiology/vascular medicine specialists assessed the appropriateness of several items regarding PTS management on a Likert-9 point scale, according to the RAND/UCLA method, with a two-round modified Delphi method. Findings: The panelists rated the following as appropriate for diagnosis: 1-the Villalta scale; 2- pre-existing venous insufficiency evaluation; 3-assessment three to six months after diagnosis of iliofemoral or femoro-popliteal DVT, and afterwards periodically, according to a personalized schedule depending on the presence or absence of clinically relevant PTS. The items rated as appropriate for symptom relief and prevention were: 1- graduated compression stockings (GCS) or elastic bandages for symptomatic relief in acute DVT, either iliofemoral, popliteal or calf; 2-thigh-length GCS (30-40 mmHg at the ankle) after ilio-femoral DVT; 3- knee-length GCS (30-40 mmHg at the ankle) after popliteal DVT; 4-GCS for different length of times according to the severity of periodically assessed PTS; 5-catheter-directed thrombolysis, with or without mechanical thrombectomy, in patients with iliofemoral obstruction, severe symptoms, and low risk of bleeding. The items rated as appropriate for treatment were : 1- thigh-length GCS (30-40 mmHg at the ankle) after iliofemoral DVT; 2-compression therapy for ulcer treatment; 3- exercise training. The role of endovascular treatment (angioplasty and/or stenting) was rated as uncertain, but it could be considered for severe PTS only in case of stenosis or occlusion above the inguinal ligament, followed by oral anticoagulation. Conclusions and relevance: This position paper can help practicing clinicians in PTS management.